Combination of α‐Fe2O3, CdS and reduced graphene oxide: high‐performance and recyclable visible light photocatalysis. (23rd December 2019) - Lei, Yun; Chen, Yanguang; Yu, Pengfei; He, Guangyu; Zhu, Yuanjie; Chen, Haiqun
Abstract : A magnetic heterogeneous α‐Fe2 O3 /CdS‐RGO (RGO: reduced graphene oxide) composite photocatalyst was synthesized using the one‐step hydrothermal method. The α‐Fe2 O3 and CdS nanoparticles with a diameter range of 20~60 nm were synchronously loaded/distributed on the surface of RGO. The as‐synthesized α‐Fe2 O3 /CdS‐RGO nanocomposites were analyzed using X‐ray diffraction, Fourier transform‐infrared spectra, BET surface area, scanning electron microscopy, transmission electron microscopy, UV–Vis diffusive reflectance spectra and Raman spectroscopy. Compared with the pure CdS, α‐Fe2 O3 and α‐Fe2 O3 /CdS nanoparticles, the α‐Fe2 O3 /CdS‐RGO nanocomposites expanded the adsorption range of visible‐light, and showed significant photocatalytic performance and cyclic stability for degradation of methylene blue in visible light. Also, the remarkable catalytic performances mainly depend on its special structure of the α‐Fe2 O3 /CdS‐RGO, which enabled the effective separation of the electron–hole pairs. These attractive features make the α‐Fe2 O3 /CdS‐RGO nanocomposite to be a photocatalyst with great application potential in water pollutants treatment. Abstract : In the photocatalytic process, pure CdS has a low utilization rate of visible light, poor cycle stability and difficult recovery. The manuscript introduces α‐Fe2 O3 and RGO to synthesize a new photocatalyst α‐Fe2 O3 /CdS‐RGO. The α‐Fe2 O3 and RGO can be the electronic conductor and receptors, improving the photocatalytic capacity under visible light irradiation. They also have the ability of magnetic separation and high cycle stability.